Multidisciplinary, Interdisciplinary, and Transdisciplinary (MIT) Learning Approach and Strategy Based on Indonesian National Qualification Framework (KKNI) Curriculum - Agus Zaenul Fitri; Muntahibun Nafis; Luluk Indarti (Ulumuna, 2020)
Inadequate understanding and different perspectives of Islamic higher education (PTKIN) in Indonesia particularly the graduate schools towards Multidisciplinary, Interdisciplinary, and Transdisciplinary (MIT) approaches result in ineffective implementation of Indonesian National Qualification Framework/Kerangka Kualifikasi Nasional Indonesia (KKNI) curriculum. Yet, MIT approach is highly needed to accelerate state development. MIT study has integrated character which opens to new developments of science and methodology and will possibly create new knowledge hybrids. This research investigated MIT learning strategy and approach at graduate schools of UIN Syarif Hidayatullah Jakarta, UIN Sunan Kalijaga Yogyakarta, and UIN Maulana Malik Ibrahim Malang. The policy of MIT learning aims to enable the learning process at graduate schools to produce new comprehensive discoveries on science and humanities. Based on a qualitative research method, this showed that the graduate schools had different MIT approach and strategy in learning and this was greatly influenced by lecturer’s and decision maker’s paradigms. MIT approach was chosen respond to the nature of science, realize very complex issues, synergize various disciplines of sciences, motivate multi-sector expert collaboration, and produce new products. In short, MIT practices mean collaboration and synergy among involving people either experts with non-experts or academic with non-academic staff.